Finding Sophie : a novel - Mahmood, Imran (New York : Bantam Books, 2024)
"Two parents, desperate to find their missing daughter, stand accused of murder. How far will they go to find the truth? Someone is guilty. For the last seventeen years, everything Harry and Zara King have done has been for their crown jewel, Sophie, their one and only daughter. When she goes missing, Harry and Zara will stop at nothing to find her. Someone knows what happened. The police have no leads, and as the weeks pass there's little news. Harry and Zara's suspicion of a neighbor and his involvement in Sophie's disappearance quickly becomes an obsession-and they'll do anything to get the answers to their questions. Someone will pay. When the neighbor is found dead in his apartment, Harry and Zara are arrested and charged with murder. They deny everything. Meanwhile, their precious daughter is still missing.."--.
new book 2024 spring.
Keywords: Detective and mystery stories; Novels; Psychological; Thrillers; Family life; domestic; Detective and mystery fiction; Novels; Detective fiction; Mystery fiction